2000
DOI: 10.2208/jscej.2000.661_11
|View full text |Cite
|
Sign up to set email alerts
|

Solution of Finite-Displacement Small-Strain Elasticity Problems by Removal of Rigid Body Displacements

Abstract: If rigid body displacements are properly separated from a fmite-displacement small-strain problem, the remaining deformation is within the scope of the small displacement theory. For this purpose, the rigid body displacement of each sufficiently small subdomain of an elastic body must be removed independently from other subdomains before the actual deformation occurs. This paper presents a rigorous and straightforward theoretical formulation for a numerical solution procedure based on this concept. The simplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The rigid body displacement, which occurred at 20 kN, 30 kN, and 40 kN, was corrected for accurate results. This was a common problem for geometrically nonlinear small-strain conditions [26]. As a percentage error below 10%, it was concluded that the simulation model could be accepted.…”
Section: Validationmentioning
confidence: 97%
“…The rigid body displacement, which occurred at 20 kN, 30 kN, and 40 kN, was corrected for accurate results. This was a common problem for geometrically nonlinear small-strain conditions [26]. As a percentage error below 10%, it was concluded that the simulation model could be accepted.…”
Section: Validationmentioning
confidence: 97%
“…The percentage error between simulation and previous experimental data was tabulated in Table 3. The higher percentage errors at loads 10 kN and 20 kN were due to rigid body displacement, which is a common problem for geometrically nonlinear small-strain condition [19]. This problem could been neglected since the average value of percentage error was 6.5% which was considered as an acceptable range to verify the accuracy of the model simulation.…”
Section: Validation Of Simulationmentioning
confidence: 99%